THE IMPORTANCE OF SOIL IN THE BIOSPHERE AND HUMAN LIFE - G.Makhsudova; T.Usmanova (Web of Journals Publishing, 2025)
Soil is a habitat for organisms, a source of nutrients, and plays an important role in the small biological and large geological cycle of substances. Each soil horizon consists of a mixture of organic and mineral compounds.
Keywords: Soil, biological, geological, organism, hectare, in nature, man, biosphere, wind, water, fertilizers, vegetation, industry.